2020
DOI: 10.1042/bsr20194427
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of LncRNA PVT1 inhibits the proliferation, migration and fibrosis of high glucose-induced mouse mesangial cells via targeting microRNA-93-5p

Abstract: Objective: The present study aimed to investigate the regulatory role of long non-coding RNA plasmacytoma variant translocation 1 (PVT1) on high glucose (HG)-induced mouse mesangial cells (MMCs). Methods: PVT1 expression in diabetic nephropathy (DN) mice and HG-induced MMCs was detected by qRT-PCR. EdU and Colony formation, Annexin V-PI staining, Muse cell cycle, Scratch, and Transwell assays were performed to detect the cell proliferation, apoptosis, cell cycle, migration, and invasion, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…PVT1 knockdown inhibits cellular migration, invasion, proliferation, and fibrosis. Furthermore, PVT1 knockdown blocks the PI3K/Akt/mTOR signal and promotes the apoptosis of MMCs under HG conditions by upregulating miR-93-5p (Li J. et al, 2020). Furthermore, Zhong et al (2020) validated that silencing PVT1 might relieve HGinduced FN and α-SMA expression and proliferation in hMCs by inhibiting the NF-κB pathway via the miR-23b-3p/WT1 axis.…”
Section: Lncrna Pvt1mentioning
confidence: 83%
See 1 more Smart Citation
“…PVT1 knockdown inhibits cellular migration, invasion, proliferation, and fibrosis. Furthermore, PVT1 knockdown blocks the PI3K/Akt/mTOR signal and promotes the apoptosis of MMCs under HG conditions by upregulating miR-93-5p (Li J. et al, 2020). Furthermore, Zhong et al (2020) validated that silencing PVT1 might relieve HGinduced FN and α-SMA expression and proliferation in hMCs by inhibiting the NF-κB pathway via the miR-23b-3p/WT1 axis.…”
Section: Lncrna Pvt1mentioning
confidence: 83%
“…Furthermore, lncRNA/miRNA interactions are a common regulatory strategy in RF, but the gene regulatory network is complex and is yet to be fully elucidated. For example, PVT1 and XIST could bind to miR-93-5p at the predicted site; silencing of PVT1 or XIST inhibits the fibrosis process in HG-treated MMCs or HK-2 Li J. et al, 2020). Similarly, MALAT1 and MIAT could influence cell proliferation, viability, migration, and the EMT process by binding to miR-145 in TGF-β1-stimulated HK-2 cells (Liu B. et al, 2019;Liu et al, 2020;Wang Z. et al, 2020).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The effect of SKF38393 on cell viability, proliferation, proliferation-associated protein expression, fibrosis-associated protein expression and p-ERK1/2 activity was similar to that of PD98059 (Figs. [1][2][3][4][5][6]. This finding suggested that the DR1-CSE/H 2 S pathway inhibited MC dysfunction by inhibiting ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 80%
“…In the presence of hyperglycemia and other stimulating factors, MCs proliferate abnormally and secrete a large amount of extracellular matrix, which is deposited in the mesangial area ( 5 ). MCs can migrate to the gap between glomerular capillary endothelial cells and the basement membrane and even protrude into the surrounding capillary cavity, resulting in capillary occlusion and ultimately leading to glomerulosclerosis ( 6 ). MC proliferation serves a key role in the process of DN, but the mechanism of MC proliferation in diabetic patients is complex.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs have also been regarded as important regulators in the regulation of DN [ 11 , 12 ]. PVT1 silence reduced cell proliferation, migration, and fibrosis in DN cell model [ 13 ]; NEAT1 acted as a pro-inflammatory molecule in DN [ 14 ]. Myocardial infarction-associated transcript (MIAT) downregulation has been correlated to the renal tubular epithelial injury in DN [ 12 ], and MIAT could enhance cell viability in high glucose (HG)-treated renal tubular cells by increasing the expression of Nrf2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%